The Influence Of Content Marketing On Brand Awareness, Brand Image, And Skincare Purchase Intention - Syifa Azqia, Syifa; Nora, Liza (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the influence of content marketing on purchase intention of Somethinc skincare products in the Greater Jakarta area by considering the mediating role of brand awareness and brand image. Content marketing strategy is considered an effective approach in building relationships with consumers and forming positive perceptions of the brand. This study uses a quantitative approach with an associative method. Data were collected through a closed-ended questionnaire from 196 respondents and analyzed using Structural Equation Modeling (SEM) techniques with the help of SmartPLS software. The results show that content marketing has a significant effect on purchase intention both directly and indirectly through brand awareness and brand image. In addition, it was found that brand awareness influences brand image, which in turn strengthens the influence on purchase intention. This study concludes that an effective content marketing strategy must be able to create strong brand awareness and image to increase consumer purchase intention. These findings provide theoretical contributions to the development of digital marketing strategies as well as practical implications for local skincare industry players in creating content that can attract attention, build emotional connections, and encourage consumer purchasing decisions.